Large displacement numerical study of 3D plate anchors. Issue 4 (20th March 2020) - Ceccato, Francesca; Bisson, Alberto; Cola, Simonetta
Abstract: This paper presents a numerical study carried out in the context of the development of a new application of plate anchors for landslide stabilisation. The plates are positioned on the slope's ground surface and linked to a deeper stable layer with a steel grouted bar, thus acting as discontinuous elements contrasting the slope movement. This technique is less expensive compared to standard retaining structures, especially in medium and deep landslides. Moreover, plate anchors can bear large displacements of the unstable moving mass without losing efficiency. Evaluating the stabilising force and its optimisation in relation to the plate shape are of great interest. Numerous studies have investigated the bearing capacity of rectangular and circular thin plates at small strains, but the performance of alternative shapes, such as cones or truncated cones, has never been considered. The numerical study here presented applies the Material Point Method to investigate the behaviour of plate anchors with different 3D shapes at large displacements. The numerical model is validated with the results of some small-scale laboratory tests. The pull-out resistance, the soil stress and displacement fields around the plate and the group effect have been investigated, thus obtaining preliminary indications for the design of these elements.